The Digital Marketing Communication Strategy of the DIY Tourism Office through Instagram @visitingjogja in Improving the Quality of Tourism Visit in 2024 - Dimas Khoirul; Nur Sofyan (Jogjakarta Communication Conference (JCC), 2026)
The tourism sector is a key pillar of the Special Region of Yogyakarta's (DIY) economy. In 2024, the number of tourist visits increased significantly, but this was not accompanied by an improvement in visit quality, as evidenced by a decrease in the length of stay. This study aims to analyze the digital marketing communication strategies of the DIY Tourism Office through its Instagram account @visitingjogja in response to this situation. This study employs a descriptive qualitative method, collecting data through in-depth interviews and document analysis, and validating through source triangulation. The results indicate that the strategies involved content collaboration with third parties, the use of digital ads and influencers to expand reach, and the presentation of event content, night tourism, and travel guides to encourage longer stays. These strategies successfully increased audience attention and interest, but have not yet fully succeeded in encouraging tourists to stay longer. This is influenced by time constraints, budget limitations, and suboptimal social media engagement. This study concludes that digital marketing via Instagram can increase tourist interest but has not yet directly improved the quality of visits.